Quality Service: servqual methodology and patient satisfaction in hospitals - de la Garza-Carranza, María Teresa; Calderón-Pérez, Alejandra; Reyes-Berlanga, Mónica Lucía; García-Torres, María Angelica (Horizonte Sanitario, 2024)
Objective: Determine the relationship between the satisfaction of hospitalized patients and the quality of service in a public hospital in the State of Guanajuato, through the SERVQUAL methodology. Materials and methods: Correlational quantitative design study and validation of measurement instruments. 191 patients of four hospital service were interviewed. Results: The results confirmed that the questionnaire used meets the reliability parameters. Additionally, a multiple linear regression analysis was carried out to identify the SERVQUAL factors that influence patient satisfaction and it was found that the influential factors are tangibility, reliability, security and empathy (F=111.17, p < 0.001), which indicates a highly significant relationship. Conclusions: The SERVQUAL variables identified as influencing service quality present a positive association (tangibility, reliability and empathy). The responsiveness variable does not present a significant value in the regression. However, the security variable presents a negative association which implies that the patient perceives that there is a lack of communication in the procedures applied by the staff and the kindness with which he is cared for. Keywords: Quality control, public health, Patient Safety.